(untitled) (Global Journal of Human-Social Science, 2018)
The present work aims to show the contribution of foreign trade to economic growth in Cameroon from 1987 to 2013. It follows that foreign trade is one of the essential levers of the Cameroonian economy. The results of stationarity tests show that series imports, exports, FDI and per capita GDP are stationary. With the regression of the ordinary least squares model, we deduce that imports and exports have positive and significant impacts on economic growth in Cameroon. While trade openness has a significant and negative impact on Cameroon’s economic growth.